Enzymatically dissociated muscle fibers display rapid dedifferentiation and impaired mitochondrial calcium control - Gineste, Charlotte; Youhanna, Sonia; Vorrink, Sabine U.; Henriksson, Sara; Hernández, Andrés; Cheng, Arthur J.; Chaillou, Thomas; Buttgereit, Andreas; Schneidereit, Dominik; Friedrich, Oliver; Hultenby, Kjell; Bruton, Joseph D.; et al. (iScience, 2022)
Cells rapidly lose their physiological phenotype upon disruption of their extracellular matrix (ECM)-intracellular cytoskeleton interactions. By comparing adult mouse skeletal muscle fibers, isolated either by mechanical dissection or by collagenase-induced ECM digestion, we investigated acute effects of ECM disruption on cellular and mitochondrial morphology, transcriptomic signatures, and Ca2+ handling. RNA-sequencing showed striking differences in gene expression patterns between the two isolation methods with enzymatically dissociated fibers resembling myopathic phenotypes. Mitochondrial appearance was grossly similar in the two groups, but 3D electron microscopy revealed shorter and less branched mitochondria following enzymatic dissociation. Repeated contractions resulted in a prolonged mitochondrial Ca2+ accumulation in enzymatically dissociated fibers, which was partially prevented by cyclophilin inhibitors. Of importance, muscle fibers of mice with severe mitochondrial myopathy show pathognomonic mitochondrial Ca2+ accumulation during repeated contractions and this accumulation was concealed with enzymatic dissociation, making this an ambiguous method in studies of native intracellular Ca2+ fluxes.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cell biology; Cellular physiology; Developmental biology; Functional aspects of cell biology